Electronic structure of Ti1−xFexO2−δ thin films with oxygen vacancies probed by soft X-ray spectroscopy. (21st April 2015) - Usui, Katsuya; Yamaguchi, Shohei; Suzuki, Naoya; Shimazu, Yuichi; Tsuchiya, Takashi; Sakai, Enju; Kobayashi, Masaki; Horiba, Koji; Kumigashira, Hiroshi; Higuchi, Tohru
Abstract: The physical properties and electronic structure of c -axis-oriented Ti1− x Fe x O2−δ thin films have been studied by soft X-ray spectroscopy. The c -axis lattice constant increases with increasing Fe concentration. Fe ions have mixed valence states of Fe 2+ and Fe 3+ with a high-spin configuration. The intensity of the unoccupied Ti 3d state decreases and that of the occupied Ti 3d state increases owing to oxygen vacancies with Fe substitution. The electronic structure in the band gap region consists of Fe 3d and Ti 3d states, which correspond to the remnant of the lower Hubbard hand. The density of states (DOS) at the Fermi level, which is closely related to electrical conductivity, is composed of the Ti 3d state. The electrical conductivity of heavily doped Ti1− x Fe x O2−δ thin films decreases owing to the electron correlation of Ti 3d electrons.